2020
DOI: 10.1002/er.5800
|View full text |Cite
|
Sign up to set email alerts
|

Parametric studies on the storage stability and aging effect of biodiesel treated with Eucalyptus oil as a cost‐effective green‐antioxidant additive

Abstract: Oxidation stability is one of the most significant fuel quality standards for biodiesel and mainly distresses the stability of biodiesel. Therefore, the present work aims to report the Eucalyptus oil (EO) as a natural green antioxidant additive to evaluate the oxidation stability of biodiesel produced from dairy waste scum, Bauhinia variegata and Butea monosperma oil. The obtained results have also been compared with the conventional synthetic antioxidant, butylated hydroxy toluene (BHT). The oxidation stabili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…The fuel storage stability is impacted by various factors like aromatic, sulfur content, oxidative, and thermal stability of fats. Particularly, the fuels with high unsaturated ester content have reduced oxidation stability due to the breakage of double bonds which leads to oxides and peroxides formation 74,75 …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The fuel storage stability is impacted by various factors like aromatic, sulfur content, oxidative, and thermal stability of fats. Particularly, the fuels with high unsaturated ester content have reduced oxidation stability due to the breakage of double bonds which leads to oxides and peroxides formation 74,75 …”
Section: Resultsmentioning
confidence: 99%
“…Previous, experimental studies have also been reported the same with the addition of synthetic and natural antioxidants which revealed that an increase in antioxidant concentration improved the oxidation stability of biodiesel. In due course of the process, the oxidation reaction particularly contributes the hydrogen from the phenolic group to interrupt the free radical chain resulting in the production of stable free radicals that do not initiate or propagate fat oxidation 74 . The scavenging effect percentage for sesame, horse gram, sweet basil, coffee, and peas was found to be 64.04%, 61.79%, 52.8%, 48.37%, and 34.83%, respectively at 500 ppm.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation